2005
DOI: 10.1258/0049475054037039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mass media campaigns on the knowledge and attitudes of pregnant Nigerian women towards HIV/AIDS

Abstract: A total of 508 women coming for antinatal care had a structured interview about the risk factors for HIV/AIDS. While most knew about HIV and that it could be transmitted sexually, knowledge of mother-to-child transmission was poor. Only 23% knew that HIV could be transmitted by breast milk. In all, 85% would not care for a relative with AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
2
5
0
Order By: Relevance
“…These findings are consistent with other studies carried out in malaria endemic areas in which knowledge on symptoms of malaria was demonstrated [13,19,20]. For example, a study investigating the prevalence of malaria among clients seeking treatment for fever and/or malaria at drug store in rural Tanzania [20] demonstrated that 24.0% of the people who experienced fever and reported to drug stores to purchase anti-malarial drugs were actually diagnosed with malaria, even though 10.7% of them had reported before that they had malaria/fever [20].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with other studies carried out in malaria endemic areas in which knowledge on symptoms of malaria was demonstrated [13,19,20]. For example, a study investigating the prevalence of malaria among clients seeking treatment for fever and/or malaria at drug store in rural Tanzania [20] demonstrated that 24.0% of the people who experienced fever and reported to drug stores to purchase anti-malarial drugs were actually diagnosed with malaria, even though 10.7% of them had reported before that they had malaria/fever [20].…”
Section: Discussionsupporting
confidence: 93%
“…II).This is comparable to the 95% reported from Calabar 10 . But awareness does not equate to understanding and accepting the modes of transmission, prevention and treatment of HIV/AIDS.…”
Section: Discussionsupporting
confidence: 84%
“…A respondent's attitude toward HIV/AIDS was categorised as negative (0-4) or positive (5-8). A respondent's level of knowledge about ART was categorised as poor (0-5) or good (6)(7)(8)(9)(10). For the respondent's attitude toward ART adherence, scores ranging from 0-3 indicated a negative attitude, whereas scores from 4-6 indicated a positive attitude.…”
Section: Methodsmentioning
confidence: 99%
“…Another study among pregnant women from Calabar, in the southern part of Nigeria, reported that they had good knowledge about HIV; however, their knowledge about mother-to-child transmission of HIV/AIDS was poor, as only 23% of the women knew that HIV could be transmitted via breast milk [10].…”
Section: Introductionmentioning
confidence: 99%